1996
DOI: 10.1021/ma9602482
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilizers for Melt Blending:  Premade Block Copolymers

Abstract: Poly(methyl methacrylate) (PMMA) was melt mixed 30:70 into polystyrene (PS) with and without symmetric P(S-b-MMA) diblock copolymers. The molecular weight of the components was varied. After 5 min of shear mixing, the PMMA was dispersed into roughly spherical, submicron particles. Particle size was measured by light scattering and transmission electron microscopy. As little as 1% copolymer led to a significant reduction in PMMA particle size, although larger amounts were needed to make the particles stable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
382
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(399 citation statements)
references
References 30 publications
17
382
0
Order By: Relevance
“…The compatibilized PET rec /EMA/EMA-GMA blend with 25 wt% of EMA and 5 wt% of EMA-GMA ( Figure 6) showed smaller particle size compared to its corresponding PET rec /EMA blend with 30 wt% of EMA, and the reduction in particle size was due to the presence of EMA-GMA compatibilizer. Macosko et al 31 attributed this to entropic repulsion of molecules located at the compatibilizer interface while balancing the Van der Waals forces and reducing coalescence. Huber et al 12 found a decrease in interfacial tension due to the presence of the compatibilizing agent that decreased the size of the dispersed phase, in which the coalescence probability drops to a negligible value.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…The compatibilized PET rec /EMA/EMA-GMA blend with 25 wt% of EMA and 5 wt% of EMA-GMA ( Figure 6) showed smaller particle size compared to its corresponding PET rec /EMA blend with 30 wt% of EMA, and the reduction in particle size was due to the presence of EMA-GMA compatibilizer. Macosko et al 31 attributed this to entropic repulsion of molecules located at the compatibilizer interface while balancing the Van der Waals forces and reducing coalescence. Huber et al 12 found a decrease in interfacial tension due to the presence of the compatibilizing agent that decreased the size of the dispersed phase, in which the coalescence probability drops to a negligible value.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…[5] The first one is the addition of a graft or block copolymer. [6][7][8][9][10][11][12] To form a graft copolymer, two strategies exist, the grafting from between polymers [13][14][15][16][17][18][19][20][21] and the grafting onto, [22][23][24][25][26][27][28][29] with a polymer bearing an initiating function previously induced by ozonolysis or irradiation. [30,31] A coupling reaction through a function can also be used to generate specific functions onto a polymer chain moiety to then start a grafting from or a grafting onto.…”
Section: Introductionmentioning
confidence: 99%
“…As result, less graft copolymer is formed at the interface. Although this amount is large enough to stabilize the phase morphology against coalescence [33], it is too small to improve the toughness of the interface, which strongly depends on the amount of block or graft copolymer added to the blends [34].…”
Section: Mechanical Propertiesmentioning
confidence: 99%